(untitled) (Annals of Medical Research, 2021)
Aim: The common cause of hereditary mental retardation is Fragile X Syndrome (FXS). This disease occurs when the trinucleotide repeat number (CGG)n in the promoter region of the Fragile X mental retardation 1 (FMR1) gene located in Xq27.3 is increased. Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disease caused by CGG repeat increase to 55-200 in the FMR1 gene. Although regulation disorders or mutations in FMR1 seem to be responsible for the pathogenesis of FXS and FXTAS, the broad phenotypic spectrum suggests that there should be some other potential genes involved. In this study, it was aimed to determine the differentially expressed genes of FMR1 premutation carriers and healthy controls by using bioinformatics techniques.Material and Methods: Gene expression profiles were downloaded from the Gene Expression Omnibus (GEO) database, which were analyzed using the Principal Component Analysis (PCA)-based unsupervised feature extraction (FE).Results: The set of 14 genes were identified that could successfully discriminate fragile X premutation carriers and healthy controls, and the majority of these genes were long non-coding RNAs (lncRNA). Conclusion: Although the results of our study should be supported by extended experimental researches, these genes have the potential to be used as biomarkers and therapeutic targets.